TINJAUAN HUKUM ATAS PEMIDANAAN TERHADAP KURIR NARKOTIKA BERDASARKAN UNDANG-UNDANG NO.35 TAHUN 2009 TENTANG NARKOTIKA - I Ketut Surya Prabawa; Lasmauli Noverita Simarmata (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
The phenomenon of cross-border drug couriers reflects the complexity of organized crime involving diverse actors, including women and minors. Many are recruited through economic pressure, personal relationships, or exploitation, yet Indonesia’s legal system tends to impose harsh penalties without proportionally assessing individual roles. This study adopts a normative juridical approach using descriptive and prescriptive methods to examine national regulations, case studies, and comparisons with the Netherlands' drug policy. The findings show that overly repressive approaches fail to deliver substantive justice, especially for minor-role offenders. The Dutch model, which incorporates harm reduction and actor differentiation, offers a more humane alternative. Based on this, the study recommends reformulating Indonesia’s drug crime policies by integrating role-assessment mechanisms and promoting rehabilitative approaches for non-central actors. These steps are crucial to building a more just, proportional, and human rights–oriented criminal justice system.